Expression of Caytaxin Protein in Cayman Ataxia Mouse Models Correlates with Phenotype Severity - Sikora, Kristine M.; Nosavanh, LaGina M.; Kantheti, Prameela; Burmeister, Margit; Hortsch, Michael (PLOS ONE, 2012)
Caytaxin is a highly-conserved protein, which is encoded by the Atcay/ATCAY gene. Mutations in Atcay/ATCAY have been identified as causative of cerebellar disorders such as the rare hereditary disease Cayman ataxia in humans, generalized dystonia in the dystonic (dt) rat, and marked motor defects in three ataxic mouse lines. While several lines of evidence suggest that Caytaxin plays a critical role in maintaining nervous system processes, the physiological function of Caytaxin has not been fully characterized. In the study presented here, we generated novel specific monoclonal antibodies against full-length Caytaxin to examine endogenous Caytaxin expression in wild type and Atcay mutant mouse lines. Caytaxin protein is absent from brain tissues in the two severely ataxic Atcayjit (jittery) and Atcayswd (sidewinder) mutant lines, and markedly decreased in the mildly ataxic/dystonic Atcayji-hes (hesitant) line, indicating a correlation between Caytaxin expression and disease severity. As the expression of wild type human Caytaxin in mutant sidewinder and jittery mice rescues the ataxic phenotype, Caytaxin’s physiological function appears to be conserved between the human and mouse orthologs. Across multiple species and in several neuronal cell lines Caytaxin is expressed as several protein isoforms, the two largest of which are caused by the usage of conserved methionine translation start sites. The work described in this manuscript presents an initial characterization of the Caytaxin protein and its expression in wild type and several mutant mouse models. Utilizing these animal models of human Cayman Ataxia will now allow an in-depth analysis to elucidate Caytaxin’s role in maintaining normal neuronal function.